Diet supplementation with phytase on performance of broiler chickens - Lelis,Guilherme Rodrigues (2012)
The assay was carried out to determine the effect of phytase supplementation on performance of broilers from 1 to 21 and 1 to 40 days of age. Twelve hundred and fifty male broilers (Ross) were distributed in a randomized experimental design, with five treatments, 10 repetitions and 25 birds per experimental unit. The treatments consisted of evaluating the phytase supplementation in diets with reductions in nutritional levels, compared with the positive control. The nutrient contents in negative controls one and two were reduced progressively and these diets were supplemented with phytase levels of 250 and 500 ftu/kg of the diet, respectively. Two diets were formulated: pre-starter/starter, 1-21 days, and growth/finishing, from 21 to 40 days). In both phases, with the phytase supplementation in diets that had their nutritional levels reduced (negative control one + 250 ftu and negative control two + 500 ftu), feed intake, weight gain and feed conversion of the birds were similar to the positive control. In the period from 1 to 40 days of age, with the diets supplemented with phytase, the productive efficiency index of the birds was similar to that of the positive control group. Supplementation with 250 ftu/kg and 500 ftu/kg phytase in diets with reduced nutritional levels improved broiler performance, resulting in parameters similar to those shown by broilers fed with the diet with normal levels of nutrients.